Interconnected effects of witnessing household violence, food insecurity, and mental health among peri-urban Cape Town youth: A mediation analysis. - Hartmann, Miriam; Stoner, Marie C. D.; Giovenco, Danielle; Ekström, Anna Mia; Hatcher, Abigail M; Zondi, Yanga Zembe; Qwabe, Nontembeko; Pettifor, Audrey; Bekker, Linda-Gail; Kågesten, Anna E (Journal of Child & Adolescent Mental Health, 2026)
Background: In sub-Saharan Africa, young people face high burdens of food insecurity and sexual and gender-based violence (SGBV), both linked to poor mental health. Objective: This study tested whether food insecurity predicts common mental disorders through household SGBV, and conversely, whether SGBV predicts common mental disorders through food insecurity. Method: Data were drawn from 534 participants aged 13 to 25 years in the longitudinal Bidirectional, Upbeat communication and Differentiated Distanced care for Young people (BUDDY) cohort study in Cape Town (2021–2022), surveyed at baseline, three months follow-up, and six months follow-up. Results: At six months follow-up, 24% reported common mental disorder symptoms, 52% had experienced food insecurity, and 33% had witnessed household SGBV. When food insecurity was modelled as the primary exposure, it was not associated with common mental disorders at six months follow-up (OR = 1.00; p = 0.99), and SGBV did not mediate this relationship (Average Direct Effect (ADE) = -0.05; Average Causal Mediated Effect (ACME) = 0.02). In contrast, when witnessing SGBV was the exposure, it was strongly associated with common mental disorders (OR = 2.19; p = 0.006). Food insecurity at three months follow-up was more common among those exposed to SGBV at baseline (OR = 1.55; 95% CI [1.06–2.27]; p = 0.024). Mediation analysis indicated most of SGBV ' s effect on common mental disorders was direct (ADE = 0.17; 95% CI 0.05–0.30), with only a small proportion mediated by food insecurity (5%). Conclusion: Findings were contrary to our primary hypothesis that food insecurity would drive common mental disorders via SGBV. Instead, household SGBV emerged as the stronger predictor of common mental disorders, with food insecurity playing a modest role. Preventing household violence may be critical to improving youth mental health, while research should further examine food insecurity's mental health impacts across contexts and timeframes.